2022
DOI: 10.1002/ejoc.202101542
|View full text |Cite
|
Sign up to set email alerts
|

Cover Feature: Nickel‐Catalyzed Aminofluoroalkylation of Alkenes: Access to Difluoroalkylated N‐Containing Heterocyclic Compounds (Eur. J. Org. Chem. 1/2022)

Abstract: The Cover Feature shows the nickel‐catalyzed aminofluoroalkylative cyclization reaction with unactive alkenes and iododifluoromethyl ketones for the synthesis of difluoroalkyl cyclic amines. The stone in the picture represents the flask filled with two reaction substrates. The Ni sword is the catalyst used to activate and accelerate the reaction, delivering the target compounds difluoroalkyl cyclic amines. More information can be found in the Full Paper by J. Wu, F. Wu et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Wu et al has quite recently reported the ATRA-type reaction of 2,2-difluoro-2-iodoacetophenones to N -(ω-alkenyl)anilines catalyzed by Ni(acac) 2 /phen in the presence of K 2 CO 3 in dioxane at 100 °C. 11 This nickel catalyst system was applied to the reaction of 1a and 2a . However, 3aa was not detected, and the starting materials were recovered unreacted.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al has quite recently reported the ATRA-type reaction of 2,2-difluoro-2-iodoacetophenones to N -(ω-alkenyl)anilines catalyzed by Ni(acac) 2 /phen in the presence of K 2 CO 3 in dioxane at 100 °C. 11 This nickel catalyst system was applied to the reaction of 1a and 2a . However, 3aa was not detected, and the starting materials were recovered unreacted.…”
Section: Resultsmentioning
confidence: 99%
“…Similar transformations, proceeding under Pd‐catalysis were developed by Fuchikami in 1987 [156] . Recently, intramolecular aminofluoroalkylation of alkenes with iododifluoromethyl ketones was realized under nickel catalysis [157] . Depending on the length of the tether between amine and olefinic fragments aziridenes, pyrrolidines or piperidines were obtained in good yields.…”
Section: Cascade Fluoroalkylation/cyclizationmentioning
confidence: 89%
“…9 Among them, nickel was employed and in 2022 Wu and co-workers reported a nickel-catalyzed aminofluoroalkylative cyclization of unactive alkenes (15) with iododifluoromethyl ketones (14) to afford versatile difluoroalkylated nitrogen-containing hetorocycles including aziridines (18), as shown in Scheme 4. 10 According to the authors, the transformation proceeds through a radical mechanism. Upon treatment with the Ni-catalyst and base, iododifluoromethyl ketones ( 14) are transformed into inter-Scheme 1 Flow BDMS generation/alkene sulfobromination/aziridination sequence.…”
Section: Aziridination Of Olefinsmentioning
confidence: 99%